Understanding Reading Retardation Cognitive Aspects - Leong, Che Kan. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
The paper discusses research on cognitive processing of disabled readers (mean age 9 years) within a brain-behavior framework and offers some projections into the future. The author focuses on children with severe reading disablility or reading retardation although reference to "backward" readers is also included. The delineation of subgroups of disabled readers, the explication of perceptual versus verbal deficits in these children, and especially differential remediation are seen as necessary continuing tasks for the years ahead. (Author/SBH)
ERIC Note: Paper presented at the World Congress on Future Special Education (First, Stirling, Scotland, June 25 - July 1, 1978).
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Processes; Educational Research; Elementary Education; Learning Disabilities; Reading Difficulty; Speeches/Meeting Papers